Characterisation of PfCZIF1 and PfCZIF2 in Plasmodium falciparum asexual stages. Issue 1 (January 2023) - Balbin, Juan M.; Heinemann, Gary K.; Yeoh, Lee M.; Gilberger, Tim-Wolf; Armstrong, Mark; Duffy, Michael F.; Gilson, Paul R.; Wilson, Danny W.
Graphical abstract: Highlights: Malaria C3H1 zinc finger proteins PfCZIF1 and 2 have similar stage expression. Both C3H1s could be truncated individually and partially in tandem. Inability to knock-out both shows asexual parasite growth requires at least one. Loss of PfCZIF2 led to changes in gene expression for exported proteins. Abstract: Plasmodium falciparum exerts strong temporal control of gene expression across its lifecycle. Proteins expressed exclusively during late schizogony of blood stages, for example, often have a role in facilitating merozoite invasion of the host red blood cell (RBC), through merozoite development, egress, invasion or early establishment of infection in the RBC. Here, we characterise P. falciparum C3H1 zinc finger 1 ( Pf CZIF1, Pf 3D7_1468400) and P. falciparum C3H1 zinc finger 2 ( Pf CZIF2, Pf3D7_0818100) which we identified as the only C3H1-type zinc finger proteins with peak expression at schizogony. Previous studies reported that antibodies against Pf CZIF1 inhibit merozoite invasion, suggesting this protein may have a potential role during RBC invasion. We show using C-terminal truncations and gene knockouts of each of Pfczif1 and Pfczif2 that neither are essential for blood stage growth. However, they could not both be knocked out simultaneously, suggesting that at least one is needed for parasite growth in vitro. Immunofluorescence localisation of Pf CZIF1 and Pf CZIF2 indicated that both proteins occur in discrete foci on the periphery of the parasite's cytosol and biochemical assays suggest they are peripherally associated to a membrane. Transcriptomic analyses for the C-terminal truncation mutants reveal no significant expression perturbations with Pf CZIF1 truncation. However, modification of Pf CZIF2 appears to modify the expression for some exported proteins including Pf KAHRP. This study does not support a role for Pf CZIF1 or Pf CZIF2 in merozoite invasion of the RBC and suggests that these proteins may help regulate the expression of proteins exported into the RBC cytosol after merozoite invasion.